An integrated epidemiological-economic analysis of foot and mouth disease: Applications to the southern cone of South America - Rich, Karl M.; Winter-Nelson, A. (Wiley, 2007)
Animal disease outbreaks impose significant economic costs that evolve over space and time, but few studies have explicitly modeled their temporal and spatial impacts. Using an integrated epidemiological-economic model, this article demonstrates a methodology that captures the dynamic and spatial effects of animal disease. The model is applied to foot-and-mouth disease in the Southern Cone of South America. The results demonstrate the benefits of spatially sensitive policies in which certain regions within the Southern Cone employ different, coordinated interventions. Further, they highlight policy relevant differences between the dominant short-run and long-run control options.